Peran Perempuan Dalam Perdagangan Tradisional Tinjauan Hukum Keluarga Islam Terhadap Pedagang Perempuan Di Pasar Gamalama Ternate - Nurhasa, Edi Jain; Alimuddin, Harwis (Jurnal Ilmiah Wahana Pendidikan, 2025)
Women play a significant role in traditional trade, including at the Gamalama Market in Ternate. They not only contribute to the family economy but also play a role in maintaining the sustainability of traditional markets. From the perspective of Islamic Family Law, women are allowed to work and trade as long as they fulfill their family obligations and uphold the values of Sharia. Women have a strategic role in supporting the family economy while facing various social and legal challenges. This research aims to analyze the role of women in traditional trade at the Gamalama Market through the lens of Islamic Family Law. The research method used is a qualitative approach with data collection techniques including observation, interviews, and literature studies. The results of the study indicate that although Islam provides freedom for women to trade, they face various challenges, such as the dual burden of family responsibilities and a lack of adequate legal protection. Women traders make significant contributions to meeting family needs and strengthening the community's economy, which aligns with the principles of justice and equality in Islamic Family Law. With this study, it is hoped to provide insights for the government and policymakers in formulating policies that better support women's roles in traditional trade. Additionally, this research also contributes to enriching the literature on the role of women in Islamic economics and Islamic Family Law.